Hopf Bifurcation from New-Keynesian Taylor Rule to Ramsey Optimal Policy - Jean-Bernard Chatelain; Kirsten Ralf (Macroeconomic Dynamics, 2020)
This paper compares different implementations of monetary policy in a new-Keynesian setting. We can show that a shift from Ramsey optimal policy under short-term commitment (based on a negative feedback mechanism) to a Taylor rule (based on a positive feedback mechanism) corresponds to a Hopf bifurcation with opposite policy advice and a change of the dynamic properties. This bifurcation occurs because of the ad hoc assumption that interest rate is a forward-looking variable when policy targets (inflation and output gap) are forward-looking variables in the new-Keynesian theory.
Keywords: E47; E52; E58; E43; C61; C62; 330; Taylor rule; Bifurcation; Ramsey optimal policy; New-Keynesian Model